Potential positive effects of bariatric surgery on healthcare resource utilisation. Issue 11 (5th July 2021) - Chadwick, Chiara; Burton, Paul R.; Playfair, Julie; Shaw, Kalai; Wentworth, John; Liew, Danny; Fineberg, Daniel; Way, Andrew; Brown, Wendy A.
Abstract: Background: To determine whether a bariatric surgical procedure is associated with a reduction in healthcare utilisation among patients with obesity and high pre‐procedural healthcare needs. Methods: Design: Retrospective cohort study. Setting: Tertiary Victorian public hospital. Participants: Twenty‐nine adults who underwent publicly funded primary bariatric surgery between 2008 and 2018 at the Alfred Hospital, Melbourne and had high resource use over the year prior to surgery, defined as at least two of ≥3 hospital admissions, ≥7 inpatient bed days for obesity‐related co‐morbidities or inpatient hospital costs ≥$10 000. Main outcome measures: Change in inpatient and outpatient resource use. Results: After 1 year following bariatric surgery, total hospital bed days decreased from 663 to 80 and the median (Q1, Q3) per patient decreased from 7 (4.5, 15) to 5 (2.25, 9.75) ( p  = 0.001) and the total number of hospital admissions fell from 118 to 67 ( p  < 0.001). The median cost of inpatient care decreased from $11 405 ($4408, $22251) to $3974 ($0, $4325) per annum ( p  < 0.001). The total and median number of outpatient attendances did not significantly change 12 months after bariatric surgery, but the demand for outpatient services unrelated to bariatric surgery declined by a median of four visits per patient ( p  = 0.013). Conclusions: The evidence from this small pilot study suggests that Bariatric surgery has the potential to decrease resource use and inpatient hospital costs over a 1‐year time frame for obese patients with high resource use. These data will be used to design a prospective randomised controlled trial to provide more definitive information on this important issue. Abstract : A retrospective cohort analysis of high‐resource‐consuming obese patients who underwent primary bariatric surgery in a high‐volume tertiary Victorian hospital. The results demonstrate significant direct health resource savings within 1 year of surgery.